An Optimal Semantic Network-Based Approach for Web Service Composition with QoS - Naji Hasan.A.H; Gao Shu; AL-Gabri Malek; Jiang Zi-Long (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
As the spread of web services, the composition of web services becomes a hot topic on both the academia and IT domains. The composition of services depends on the semantic descriptions, which describe the functionality of the services, provided by the owners of services and on the description of the consumer’s requests. The composition also depends on non-functional descriptions (QoS). In this paper, we present an approach of web services composition based on both semantic description and QoS. The proposed approach builds a network of web services by matchmaking the semantic concepts in OWL-S, using the outputs-inputs similarity between services. Then, many composed assemblies can be created by combining web services in the semantic network according to consumer’s needs. Those composed assemblies will be ranked by the QoS that provided by the consumer and the suitable one will be sent back to the consumer. This approach takes the advantages from Pellete DL Reasoner, depth-first and forward chaining algorithms. A prototype and a study case are presented to illustrate the efficiency of our approach. DOI: http://dx.doi.org/10.11591/telkomnika.v11i8.3068